SHOES FOR THE THEATRE COSTUMES OF FAIRYTALE CHARACTERS OF THE MUSICAL "PINOCCHIO": A SYNTHESIS OF FASHION AND STAGE AND DECORATIVE ART - LYPSKI, TIMOFEY; GARANINA, OLGA; BABYCH, АNTONINA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The purpose of the work is to study the state of potential opportunities, develop a project concept and implement the designer's bold ideas in the manufacture of footwear for theatrical costumes of fairy-tale characters.An analysis of historical and journalistic and formulation of conclusions.An analysis of research and publications of scientists and practitioners was carried out according to the topic. A historical excursion into the emergence, development and evolution of theatrical costume and footwear as its component was presented. Stylistic and constructive features and requirements for footwear for various fairy-tale characters were described. The complete and step-by-step process of manufacturing products based on a creative source and sketches was studied theoretically and experimentally in order to improve the design and functionality of footwear at the stages of product creation.Product requirements, ready-made material maps, technological maps for performing operations for assembling and finishing finished products were developed. The relevance of this project was theoretically proven.The possibility of using different groups of materials and methods of finishing materials and finished products for the production of theatrical footwear for fairy-tale characters has been proven theoretically and practically.A draft project was developed based on the customer's creative idea, a line of theatrical footwear for fairy-tale characters for the musical "Pinocchio" was manufactured at Litini LLC, and the footwear was tested at the Kyiv Opera and Ballet Theater. Based on the results of the product testing, an organoleptic examination was conducted to confirm the compliance of the developed products with the concept of the performance, the director's idea, and the theme of the musical, as well as the quality and comfort of the products when worn. The high quality and wear resistance of the footwear was confirmed.
Keywords: stage footwear; design; material; concept; quality; style